Systemic effects of CFTR modulator therapy in cystic fibrosis: implications for organ function and quality of life - Zdunek, Marta; Stodulski, Maciej; Bulicz, Anna; Kasprzycka, Izabela; Kukla, Monika; Kowalczyk, Olga; Dziarnowska, Joanna; Kozłowski, Sebastian; Fiks, Justyna; Kmiecik, Izabela (Quality in Sport, 2026)
Background: Cystic fibrosis (CF) is a chronic autosomal recessive disease caused by CFTR mutations, leading to impaired chloride and bicarbonate transport and the production of thick secretions. This results in progressive damage, mainly in the respiratory and gastrointestinal systems. CFTR modulators have recently transformed CF treatment by targeting the underlying defect. Aim: To review the pathophysiology and clinical manifestations of CF and evaluate the effects of CFTR modulators on pulmonary and extrapulmonary systems. Materials and Methods: A narrative literature review was conducted using PubMed and Google Scholar with keywords such as “cystic fibrosis”, “CFTR mutations”, “clinical manifestations”, and “CFTR modulators”. Results: CFTR modulator therapies, have demonstrated significant clinical benefits. These include improvement in lung function, reduction in pulmonary exacerbations, and enhanced quality of life. Additionally, extrapulmonary effects were observed, such as partial restoration of pancreatic function, reduction of gastrointestinal symptoms and inflammation, improvement in nutritional status, and positive effects on reproductive health. Conclusions: CFTR modulators represent a major advancement in CF therapy, improving both pulmonary and systemic outcomes. However, limitations such as variable response and limited access remain. Further studies are needed to assess long-term effects.